A Joint Replenishment Inventory Model to Control Multi-Item Medicines with Consideration of Space Requirements in the Hospital - William, W.; Ai, T.J.; Lee, W. (International Journal of Industrial Engineering and Engineering Management, 2020)
Medicines can be considered the most widely used medical expenditures in hospitals. To reduce the medicines expenses in the hospital, the term of inventory control is applied. Medicines must be controlled by considering the expiry dates and the probabilistic demand from the customers. Therefore, it is necessary to develop an inventory model that can be suitable to control medicines by minimizing the expired medicines, total inventory costs, and dealing with unpredictable demand. The purpose of this research is to develop an inventory model for determining optimum replenishment time and order quantities and space requirements for multi-item medicines with consideration of expiry dates of the medicines and all medicines are being purchased in a single purchase order so that the total inventory costs in hospitals can be minimized. The result is that the proposed inventory model results in optimum space requirements and the lowest inventory costs. Therefore, hospitals must order medicines based on the optimum order quantity.